Cell surface α2, 3-linked sialic acid facilitates Zika virus internalization. Issue 1 (1st January 2019) - Tan, Chee Wah; Huan Hor, Catherine Hong; Kwek, Swee Sen; Tee, Han Kang; Sam, I-Ching; Goh, Eyleen L. K.; Ooi, Eng Eong; Chan, Yoke Fun; Wang, Lin-Fa
ABSTRACT: The emergence of neurotropic Zika virus (ZIKV) raised a public health emergency of global concern. ZIKV can cross the placental barrier and infect foetal brains, resulting in microcephaly, but the pathogenesis of ZIKV is poorly understood. With recent findings reporting AXL as a type I interferon antagonist rather than an entry receptor, the exact entry mechanism remains unresolved. Here we report that cell surface sialic acid plays an important role in ZIKV infection. Removal of cell surface sialic acid by neuraminidase significantly abolished ZIKV infection in Vero cells and human induced-pluripotent stem cells-derived neural progenitor cells. Furthermore, knockout of the sialic acid biosynthesis gene encoding UDP-N-acetylglucosamine-2-epimerase/N-acetylmannosamine kinase resulted in significantly less ZIKV infection of both African and Asian lineages. Huh7 cells deficient in α2, 3-linked sialic acid through knockout of ST3 β-galactoside-α2, 3-sialyltransferase 4 had significantly reduced ZIKV infection. Removal of membrane-bound, un-internalized virus with pronase treatment revealed the role of sialic acid in ZIKV internalization but not attachment. Sialyllactose inhibition studies showed that there is no direct interaction between sialic acid and ZIKV, implying that sialic acid could be mediating ZIKV-receptor complex internalization. Identification of α2, 3-linked sialic acid as an important host factor for ZIKV internalization provides new insight into ZIKV infection and pathogenesis.